Assessment of the Measures Implemented in Bulgarian Legislation to Reduce the Content of Nitrates in Groundwater Used for Public Water Supply - Emilia Bankova (Journal of Biomedical & Clinical Research)
The article analyzes the application of the current documents related to reducing nitrate pollution of groundwater bodies used for public water supply in the Pleven administrative region. The requirements of the European legislation are fully implemented in the Bulgarian legislation, but the legislative measures have not led to quick and permanent results, i.e., small drinking water sources contaminated with nitrates still exist. Special attention should be paid to the diffusive sources of pollution (mineral fertilization of soils) since they are of the most significant importance in groundwater contamination with nitrates. For settlements with permanently elevated nitrate content (over 50 mg/L), it is necessary to consider the application of an individual approach in dealing with this long-standing problem: changing the water source, mixing the water from two neighboring water sources or implementing specific purification methods (biological denitrification, ion exchange resins, etc.). We analyzed the data from the monitoring of drinking water carried out by the Regional Health Inspectorate – Pleven and found that in the Pleven region, there are 17 towns or villages (out of a total of 123) for which some of the listed measures should be foreseen. The district’s relative share of the exposed population is 3.2%, comparable to the country’s exposed population for 2004-2007.